Exploring public awareness, influencing factors and policy implications towards microplastic pollution: perspectives from Malaysia - Praveena, Sarva Mangala (Elsevier BV, 2024)
Studies have shown the extent of plastic waste impacts, which impose risks to human health and ecological systems. Public awareness about microplastic pollution's behavioural aspects, however, has been mixed. Thus, this study sought to determine the Malaysian public's level of awareness about microplastic pollution and the factors influencing their willingness to reduce microplastics emissions. In addition, public reaction toward current microplastic reduction policy was ascertained. Accordingly, snowball sampling technique utilising 750 survey respondents was carried out. While most respondents demonstrated a good level of plastics waste awareness, only 54.2 have heard of the term “microplastics.” More than 50 of respondent's perceived microplastics associated risks and 88.7 were willing act to reduce its emissions into the environment. Factors influencing public willingness to reduce microplastics emissions included level of concern about microplastics emissions levels, perceived impact on human health, behaviour of microplastics emissions, and socioeconomic factors (gender, occupation and respondent location). A high percentage of respondents (94.6) support policies to reduce microplastic pollution but acknowledge impediments to this end, to wit, poor waste management, indiscriminate dumping, lack of information sharing, and uncertainty about government policies on plastics and microplastics. The present study has engendered valuable insights into public knowledge gaps and areas to focus educational initiatives and awareness campaigns both in Malaysia and globally.